DETECTION OF RIFAMPICIN RESISTANT MYCOBACTERIUM TUBERCULOSIS ISOLATES USING GENEXPERT IN CLINICAL SPECIMENS OF VARIOUS BODY FLUIDS RECEIVED IN CMH, MULTAN (The Research of Medical Science Review, 2025)
There is a higher burden of tuberculosis in low- and middle-income countries. Improved and rapid diagnostic testing, using Xpert MTB/RIF that detects both tuberculosis and rifampicin resistance. This frequency study was conducted at Microbiology Department of Combined Military Hospital, Multan where MTB GeneXpert assay was performed as per recommended guidelines. Frequency of tuberculosis was found to be 18.3% and frequency of Rifampicin resistance as 9.3 %. Tuberculosis endemic countries like Pakistan where MDR and XDR tuberculosis is prevalent at increased frequency, there is increased need for early, rapid and accurate diagnostics tools for tuberculosis diagnosis, treatment and follow up to end this endemic.